An Analysis of Word Stress in The Devil Wears Prada Movie - Ratu Zahra (Lembaga Yasin AlSys, 2026)
Although word stress has received considerable attention in pronunciation and phonological studies, research specifically examining word stress patterns in authentic workplace communication represented through movies remains limited. This study aims to analyze the use and communicative functions of word stress in The Devil Wears Prada. A qualitative approach with a descriptive research design was employed. The data consisted of selected words containing identifiable primary stress patterns found in the movie script and audio dialogues. Data were collected through observation and note-taking by repeatedly watching the movie, examining the script, and identifying words with prominent stress patterns. The data were analyzed using qualitative content analysis by classifying stress placement, identifying word classes, and interpreting the communicative functions of stress in the dialogues. The findings show that word stress appears in nouns, adjectives, and occupational terms, including “fashion,” “assistant,” “designer,” “important,” and “magazine.” The analysis indicates that accurate stress placement helps speakers emphasize key information, clarify meaning, express communicative intentions, and improve speech intelligibility in workplace interactions. This study concludes that word stress functions as an important suprasegmental feature in authentic spoken discourse. The findings contribute to phonological studies by demonstrating how stress patterns operate in movie-based workplace communication and provide practical implications for English pronunciation learning by supporting the use of movies as authentic materials to improve students’ awareness of word stress and other suprasegmental features.